Pemanfaatan Teknologi Virtual Reality untuk Optimalisasi Pemasaran Produk Tenun Tradisional di Desa Sade - Baiq Handayani Rinuastuti; Bq. Saripta Wijimulawiani; Abdurrahman Abdurrahman; Arinda Cahya Farizna; Ni Made Jiantisusari; Ade Yoga Pratama (Jurnal Gema Ngabdi, 2026)
Sade, located in Central Lombok, Indonesia, is known for its rich cultural heritage, particularly in traditional weaving. However, the community faces significant challenges in marketing their woven products due to limited digital literacy and access to global markets. Most of the marketing is done through traditional methods, primarily targeting local tourists, which restricts the potential for broader market reach. The introduction of Virtual Reality (VR) technology offers an innovative solution to overcome these barriers. By providing immersive and interactive marketing experiences, VR enables consumers from around the world to engage with the woven products virtually, even without visiting the village. The project aims to empower the local community by training them in VR technology to help them promote their products globally. The methods include educating the community on VR applications, developing engaging content showcasing the weaving process and cultural stories, and integrating digital marketing strategies to expand their reach. Preliminary results indicate that VR has successfully increased the visibility of the products, improved digital skills within the community, and attracted more global interest in their woven crafts. This initiative not only helps in marketing the products but also preserves the cultural heritage of Desa Sade while enhancing the economic resilience of the local community